2014
DOI: 10.1007/s00268-014-2628-6
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Burden of Cleft Lip and Palate in Rural Gujarat, India: A Population‐Based Study

Abstract: The incidence of CL with or without palate was found to be 0.7 per 1,000 live births. The large number of unoperated cases (backlog) of cleft deformities suggests a big burden of unmet need in rural India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
(42 reference statements)
2
16
0
Order By: Relevance
“…Other studies conducted in South Indian population showed similar results, indicating CL/P being the most frequently occurring cleft anomaly, thus corroborating our result [19][20][21]. A contrasting view has been promulgated by Khajanchi et al who asserted in their work that occurrence of CL was the most common cleft abnormality followed by CL/P [22]. Environmental factors have been associated with increased risk of CL/P including: consanguinity, smoking, alcohol ingestion, use of anticonvulsants during pregnancy as well as insufficient folic acid intake in the pregestational period and first trimester of pregnancy [23].…”
Section: Discussionsupporting
confidence: 91%
“…Other studies conducted in South Indian population showed similar results, indicating CL/P being the most frequently occurring cleft anomaly, thus corroborating our result [19][20][21]. A contrasting view has been promulgated by Khajanchi et al who asserted in their work that occurrence of CL was the most common cleft abnormality followed by CL/P [22]. Environmental factors have been associated with increased risk of CL/P including: consanguinity, smoking, alcohol ingestion, use of anticonvulsants during pregnancy as well as insufficient folic acid intake in the pregestational period and first trimester of pregnancy [23].…”
Section: Discussionsupporting
confidence: 91%
“…The lack of knowledge and resources leads to unacceptable delays in treatment, and many infants with orofacial clefts die of malnutrition. [5,16] Lack of treatment may have many causes: ignorance, child neglect, lack of affordability, lack of transportation, and gender bias. In some rural parts of India, sociocultural beliefs also lead to denial of medical care as a child born with a cleft is deemed as a preternatural blessing.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Infants born with CL/P in LMICs face significant barriers to treatment, which often lead to prolonged disfigurement, social stigma, speech impairment, and feeding difficulty that may result in malnutrition and even death. [4][5][6] Although CL/P is a complex condition that benefits from comprehensive care, the provision of safe, timely, and effective surgery helps to achieve a successful outcome. 5,6 Like other LMICs, India lacks reliable documentation of birth anomalies 7 ; thus, accurate estimates of the burden of CL/P in India are few.…”
mentioning
confidence: 99%
“…5,6 Like other LMICs, India lacks reliable documentation of birth anomalies 7 ; thus, accurate estimates of the burden of CL/P in India are few. 4 A multicenter hospital-based study of 94 610 births 8 reported that the incidence of CL/P was 9.3 per 10 000 births and the incidence of cleft palate was 1.7 per 10 000 births. Khajanchi et al 4 performed a populationbased assessment of the unmet need for CL/P treatment in a single district.…”
mentioning
confidence: 99%
See 1 more Smart Citation